Bottom Meson Spectroscopy in HQET - Virk, Navjot Kaur (My University, 2012)
Particles and their properties can be studied through various models and theories. These models and theo-ries are based on perturbative or non-perturbative approaches. In the present thesis, our aim is to study the heavy-light bottom mesons in the fundamental theory that involves the inclusion of two symmetries (Heavy quark symmetry and the Chiral symmetry) and combined effect of these two is called the heavy quark effective theory. One of the main aim of this thesis is to find the unknown masses of the bottom meson sector for even and odd parities with the help of the recent available data in PDG. We used the mass formulae developed by Manohar and Wise written in terms of the HQET parameters to find the unknown non strange states of B meson. Comparison have been made with the other theoretical values in literature and with the experimental result thereby verifying the validity of this theory in estimating the masses and mass splitting of the bottom mesons in the heavy-light sector.
Keywords: HQET; Heavy quarks; Symmetries; Bottom mesons; Mass Spllitings